Pengaruh Metode Pendidikan Sebaya terhadap Tingkat Pengetahuan Tentang Pemeriksaan Payudara Sendiri (SADARI) Pada Remaja Putri Di SMA Negeri 1 Kubu : Effect of Peer Education Method on Knowledge Level About Breast Self Examination (SADARI) in Adolescent Girls at SMA Negeri 1 Kubu - Ni Putu Eka Wijayanti; Made Ririn Sri Wulandari; Luh Putu Widiastini (NERS Jurnal Keperawatan, 2022)
Breast cancer is a disease that causes cells in the breast tissue to change and divide uncontrollably. BSE or breast self-examination is one of the early detection of breast cancer, but awareness of doing BSE is still low. BSE awareness can be increased by increasing knowledge first. The Bali Provincial Health Office recorded that in 2016, there were 389 cases of breast cancer in Bali, five of which were suffered by adolescents with an age range of 15-19 years. Teenagers are usually friendly and open with their peers. This study aimed to determine the effect of peer education methods on the level of knowledge about breast self-examination in adolescent girls. This study used a pre-experimental design with one group pretest posttest. The population of this study were young women who activly members of the Student Union and School Security Patrol namely 41 young women. Taking samples using total sampling, so amounted to 41 young women. The data were analyzed using the Wilcoxon Signed Rank Test to compare the results of the pretest and posttest. The results of the study obtained a p value = 0.000 which indicates that the peer educator methods can increase adolescent girl’s knowledge about BSE, it is recommended for health workers and educational institutions to be able to form adolescent cadres who are ready to provide direct health counseling to other adolescents either at school or in community.